The regulation of safety zones in the exclusive economic zone and the continental shelf. Brief reference to Cuba - Torres Tesoro, Miguel E. (REVISTA ELECTRONICA IBEROAMERICANA, 2022)
According to international law, the coastal State may establish, around artificial islands, installations and structures, safety zones in the Exclusive Economic Zone and the Continental Shelf. Appropriate measures may be taken in said Zones, to guarantee both the safety of navigation and that of the artificial islands, installations and structures. These zones have an extension of up to 500 meters around the aforementioned infrastructures, although the United Nations Convention on the Law of the Sea allows the relevant international organization to extend it. In this case is the International Maritime Organization.UNCLOS obliges to declare the Zone, however, it does not regulate the prohibition of entry and other situations that could occur within said Zone, nor the competence to detain and punish offenders of the regulations established for the Safety Zones (when the coastal States decide to establish them). Through comparative studies and the international instruments in force today, we intend to find those regulations that allows States to extend its jurisdiction to the Safety Zones in EEZ and Continental Shelf. Of course, limited to the nature of the operations of the artificial islands, installations and structures.
Keywords: Safety Zones; Law of the Sea Convention; Exclusive Economic Zone; Continental Shelf; jurisdiction